2020
DOI: 10.1088/1742-6596/1529/5/052050
|View full text |Cite
|
Sign up to set email alerts
|

Weighting Temporary Change Outlier by Modified Huber Function with Monte Carlo Simulations

Abstract: Robust method is a popular approach to dealing the existence of outliers in the data. Many researchers have applied Huber weight function. The aim of this paper is to evaluate the performance of the Huber weight function and the modification of the Huber weight function on the temporary change (TC) outliers. The data used in this paper were generated as ARMA(1,0)-GARCH(1,2) model via the Monte Carlo simulation. There are three major situations in this simulations: without weight (WW), with Huber weight (WH) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The outcome of the simulation by 30 suggested that median and median absolute deviation (MAD) or IQR could be reasonable alternatives to mean and variance. Nevertheless, this paper used the IQR/3 which was suggested by Ghani and Rahim 31 .…”
Section: Measure Of Central Tendency and Dispersionmentioning
confidence: 99%
“…The outcome of the simulation by 30 suggested that median and median absolute deviation (MAD) or IQR could be reasonable alternatives to mean and variance. Nevertheless, this paper used the IQR/3 which was suggested by Ghani and Rahim 31 .…”
Section: Measure Of Central Tendency and Dispersionmentioning
confidence: 99%